Ilościowe i jakościowe mierniki w podejmowaniu decyzji zarządczych w działalności medycznej - Baran, Wioletta; Urbanek, Piotr (Qualitative and quantitative measures in the decision-making process in the health care services industry, 2006)
In order to operate efficiently each business entity needs more information than that created by financial accounting system. Managerial accounting system involves the preparation and interpretation of accounting information designed to assist managers in planning and controlling the operations of the business. The aim of the paper is to present how to organize accounting information system in the manner that is most relevant for supporting the decision-making process in institutions operating in the health care services industry. A set of qualitative and quantitative measures is presented and in the empirical part of the paper the discussion points are results of investigation conducted in numerous of health care entities both public and private ones.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1136, s. 13-27